1974
DOI: 10.1121/1.1903465
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of ultrasound. III. The irradiative behavior of simple aliphatic amines

Abstract: The ultrasonic irradiation of water was effected under an argon atmosphere with an 800-kHz transducer at several intensities. The rates of hydrogen peroxide formation were followed by spectrophotometric analyses. The results were utilized to relate intensity to reaction rate for standardization purposes. Irradiations of several alkyl amines in aqueous solution or suspension were next accomplished under conditions similar to those applied to pure water. Products included aldehydes, an alcohol, amines, an N-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…'OH + 'OH -H202 (10) 'OOH + 'OOH -H202 + 02 (11) Following the work of P. Riesz and colleagues, with the use of DMPO as spin trapping reagent, identification of the radicals escaping out of the bubble of cavitation has been performed in electron spin resonance (ESR) experiments.18 The main fraction of the H2O2 formed during water sonolysis seems to come from the 'OH and 'OOH radicals, which combine in the bubble or in the layer surrounding the bubble of cavitation in the absence of substrate19'64-65 (reactions 10, 11). The amount of H2O2 produced at each of the two frequencies was determined (Figure 4).…”
Section: H20mentioning
confidence: 99%
See 1 more Smart Citation
“…'OH + 'OH -H202 (10) 'OOH + 'OOH -H202 + 02 (11) Following the work of P. Riesz and colleagues, with the use of DMPO as spin trapping reagent, identification of the radicals escaping out of the bubble of cavitation has been performed in electron spin resonance (ESR) experiments.18 The main fraction of the H2O2 formed during water sonolysis seems to come from the 'OH and 'OOH radicals, which combine in the bubble or in the layer surrounding the bubble of cavitation in the absence of substrate19'64-65 (reactions 10, 11). The amount of H2O2 produced at each of the two frequencies was determined (Figure 4).…”
Section: H20mentioning
confidence: 99%
“…Propagation of an ultrasonic wave in liquid generates the formation of cavitation bubbles which can grow and implode under the periodic variations of the pressure field.1-4 In water, implosion and fragmentation of the bubble which collapses are the center of high-energy phenomena; temperature, pressure, and electrical discharges giving rise to H2O sonolysis with production of radical species (H*, *OH, HOO*) and direct destruction of solute. [5][6][7][8][9][10][11][12][13][14][15][16][17] Ultrasound is then a source of radicals, especially the hydroxyl radical, 'OH, the very strong and nonspecific oxidizing species which escapes out of the bubble and reacts rapidly with compounds in solution.18 -20 In relationship with water treatment, there are several reports in the recent literature which describe the ultrasonic destruction of organic compounds in water.21-31 Most of the work is performed with the help of the commercially available probe system working at 20 kHz, 32 but it has been demonstrated that for the same acoustical power the production rate of *OH is better at higher frequencies. [33][34][35][36][37] In order to determine experimental conditions that could lead to the best reaction yields, we report a study of phenol degradation with two different ultrasound systems.…”
Section: Introductionmentioning
confidence: 99%